2017
DOI: 10.3892/br.2017.913
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of urinary-to-serum human epididymis protein 4 ratio in ovarian cancer

Abstract: Abstract. Human epididymis protein 4 (HE4) is one of the best-known tumor markers for ovarian cancer (OC). Emerging evidence indicates that the evaluation of serum HE4 (S-HE4) levels may be problematic when patients have chronic kidney disease (CKD). Assaying urine for HE4 levels is non-invasive alternative for the diagnosis of OC. However, whether the combined detection of S-and urinary HE4 (U-HE4) levels distinguishes OC from CKD remains unknown. To investigate this issue, the present study recruited 31 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Twelve studies explored the diagnostic and predictive potential of proteins and metabolites in urine for OC 64‐75 . Four studies show the potential of DNA methylation profiles, miRNA expression and exosomes in urine for detection 76‐79 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies explored the diagnostic and predictive potential of proteins and metabolites in urine for OC 64‐75 . Four studies show the potential of DNA methylation profiles, miRNA expression and exosomes in urine for detection 76‐79 .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies explored the diagnostic and predictive potential of proteins and metabolites in urine for OC. [64][65][66][67][68][69][70][71][72][73][74][75] Four studies show the potential of DNA methylation profiles, miRNA expression and exosomes in urine for detection. [76][77][78][79] Although all these studies showed good performance, almost none specified which urine fraction or preservation method, if any, they used.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Details of the included studies on urine HE4 are provided in Table 2 [57][58][59][60][61]. The total number of participants involved in these five studies was 649.…”
Section: Characteristics Of Studies On Urine He4mentioning
confidence: 99%
“…The marker may be present in several isoforms with different molecular weights [1,3]; therefore, its concentration is usually expressed in pM (picomole/L). Serous HE4 concentration is strongly elevated in the case of ovarian cancer, although a certain elevation is also observed in cervical and breast cancers [4], as well as in chronic kidney disease [5]. Moreover, marker concentration strongly depends on the stage of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…HE4 exhibits good selectivity and specificity (with an ROC (receiver operating characteristic) curve with an area under the curve (AUC) value of 0.91) and strongly reacts to the disease stage [4]. It should be noted that urine HE4 concentration is much higher than the serous marker concentration, and it is significantly elevated in the case of ovarian cancer [5]. The designed biosensor appears to be suitable for the determination of HE4 in both healthy individuals and ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%